STRATEGI PENGEMBANGAN USAHA KRIPIK PISANG COKLAT UMKM DI DESA SAMBIREJO KECAMATAN WONOSALAM KABUPATEN JOMBANG - Muhammad Amirul Wahid; Ahmad Fathurrobbani; Machrus Ali; Miftahul Djanah (Indonesian Collaboration Journal of Community Services, 2023)
With the increasing number of small and medium entrepreneurs, the business competition is now getting tougher. Innovation and a good marketing strategy are needed in order to attract consumers. The development strategy is carried out so that production results develop into more innovative flavors, better production packaging, and marketing that is far more in control of the digital marketing system so that there is no lag in the digital marketing system. Sales strategies and innovations can help MSME players reach a wider market with higher-quality production standards. This community service was carried out in Sambirejo Village, Wonosalam District, Jombang Regency. The target of this activity is MSME players who need to develop the quality of their production with high economic potential and marketing development that needs to be improved. Through this activity, it was found that MSME actors had understood the development strategy process which would continue to be developed over time. With innovative production processes, attractive packaging, use of mass media, and marketplaces, MSME players have succeeded in developing markets and increasing income turnover